Realist evaluation of the impact of the research translation process on health system sustainability: a study protocol - Yvonne Zurynski; Delia Hendrie; Suzanne Robinson; Elizabeth Geelhoed; Abby Mosedale (BMJ Open, 2022)
Introduction Sustainability at a system level relates to the capacity of the system to be able to service the ongoing health needs of the population. It is a multifaceted concept encompassing both the affordability and efficiency of a system and the system’s ability to adapt and change.To address issues that currently threaten health system sustainability, healthcare leaders, policy makers, clinicians and researchers are searching for solutions to ensure the delivery of safe, value-based care into the future. The timely translation of research evidence into sustainable interventions that can be adopted into the health system is one way of bolstering the sustainability of the system as a whole. We present a protocol for the realist evaluation of a research translation funding programme to understand how the research translation process contributes to health system sustainability and value-based healthcare.Methods and analysis Underpinned by the realist evaluation framework, we will: (1) Develop the Initial Program Theory (IPT) of the research translation process; (2) Test the program theory through case study analysis; and (3) Refine and consolidate the theory through stakeholder consultation. The evaluation uses a case example of a research translation programme, chosen for its representation of a microcosm of the broader health system and the heterogeneity of service improvement activities taking place within it. Across the three phases, analysis of data from documents about the research translation program and interviews and focus groups with stakeholders and program users will draw on the context (C), mechanism (M), outcome (O) formula that is core to realist evaluation. In addition, system dynamic methods will capture the feedback loops and complex relationships among the IPT and context-mechanism-outcome configurations. This approach to evaluation of a research translation funding programme may be adapted to similar programmes operating in other settings.Ethics and dissemination Curtin University Human Research Ethics Committee, Western Australia, approved this study (approval number: HRE2020-0464). Results will be published in scientific journals, and communicated to respondents and relevant partners.